Finance basics : decode the jargon, navigate key statements, gauge performance (Boston, MA : Harvard Business Review Press, 2014)
Intimidated by corporate finance? The numbers (and the jargon) can feel overwhelming--but you have to understand them to manage effectively. "Finance Basics" explains the fundamentals simply and quickly, introducing you to key terms and concepts such as: - How to navigate financial statements- How to weigh costs and benefits- What's involved in budgeting and forecasting- How to gauge a company's financial health About HBR's 20-Minute Manager Series: Don't have much time? Get up to speed fast on the most essential business skills with HBR's 20-Minute Manager series. Whether you need a crash course or a brief refresher, each book in the series is a concise, practical primer that will help you brush up on a key management topic. Advice you can quickly read and apply, for ambitious professionals and aspiring executives--from the most trusted source in business.
Why understand finance? -- Navigating the three major financial statements. Accounting methods ; The income statement ; The balance sheet ; The cash flow statement -- Using the statements to measure financial health. Profitability ratios ; Efficiency ratios ; Liquidity ratios ; Leverage rations ; Other ways to measure financial health -- Preparing a budget. Top-down versus bottom-up budgeting ; Getting started ; Articulating your assumptions ; Quantifying your assumptions -- Calculating return on investment. Costs and benefits ; Payback period ; Net present value and internal rate of return ; Break-even analysis ; Sensitivity analysis ; Evaluating unquantifiable costs and benefits -- Tracking performance. Performance of an investment ; Performance of an existing unit ; Forecasts -- Test yourself -- Answers to test questions -- Key terms -- Learn more -- Sources.
Includes bibliographical references and index.
Keywords: Corporations -- Finance; Managerial accounting; Corporations -- Finance; Managerial accounting